Online dispute resolution in Indonesian e-commerce: Arbitration law and shariah consumer protection - Nia Melawati (UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to analyse the position of online dispute resolution (ODR) in Indonesian e-commerce from the perspective of arbitration law and assess its normative adequacy in light of the principles of shariah consumer protection. The study employs normative legal research, drawing on statutory, conceptual, and analytical approaches. Its legal materials consist of regulations on arbitration, electronic transactions, consumer protection, and digital commerce, complemented by scholarly literature on ODR, e-arbitration, and shariah consumer protection. The results indicate that ODR in Indonesian e-commerce has become an effective method for resolving numerous low-value consumer disputes. However, its legal and institutional status remains unsettled. The primary challenges pertain to the legitimacy of electronic consent, procedural equity in digital environments, the legal standing and enforceability of electronic results, and the indistinct demarcation between arbitration, complaint resolution, and platform-based redress. This article contributes by integrating arbitration law and shariah consumer protection into a single evaluative framework, thereby shifting the assessment of ODR from procedural efficiency toward substantive justice. It recommends developing a more explicit, coherent, and consumer-oriented ODR framework that strengthens transparency, informed consent, and the protection of consumers’ economic rights. This study enriches the discourse on digital dispute resolution by positioning ODR as both a legal and normative site of consumer justice.